Faktor yang Berhubungan dengan Pengetahuan Karyawan tentang Kesiapsiagaan Bencana Kebakaran di PT Trans Dana Profitri - Fahmi, Razi; Santi, Tahara Dilla; Arlianti, Nopa; Wardiati; Septiani, Riza (Jurnal EMT KITA, 2025)
Fire disaster preparedness is an important aspect in corporate risk management, especially in work environments that have the potential for fire. In 2023, there were 270 fire incidents in the Aceh region with residential fires dominating 103 incidents. The high number of fires indicates that public knowledge of fire prevention and control is still very minimal. This study aims to determine the factors related to employee knowledge of fire disaster preparedness at PT Trans Dana Profitri. This study is descriptive analytical with a cross-sectional approach. Data collection was carried out by interviews using questionnaires. The population in this study were all employees of PT Trans Dana Profitri at the Banda Aceh Representative Office and the sample was determined by the total population so that a sample of 50 employees was obtained. The study was conducted in December 2024. The statistical test used was the Chi Square Test (95%). The results of the study showed that employee knowledge about fire disaster preparedness was in the good category (74.0%), the age of employees was early adulthood (<40 years) (68.0%), their education was in the high school category (52.0%), their sources of fire information were sufficient (64.0%), their experience was in the none category (66.0%). There was a relationship between age (p = 0.001), education (p = 0.017), sources of information (p = 0.003), and work experience (p = 0.020) with employee knowledge about fire disaster preparedness at PT Trans Dana Profitri Banda Aceh Representative Office in 2024. Age, education, sources of information and work experience factors were related to employee knowledge about fire disaster preparedness at PT Trans Dana Profitri Banda Aceh Representative Office. PT Trans Dana Profitri Banda Aceh Representative Office can improve employee preparedness for fire disasters by holding routine interactive training, such as evacuation simulations and the use of fire extinguishers, as well as ensuring the dissemination of safety information through internal media and mentoring by experienced employees.